Monitoring and Protection of Power Distribution Networks with IEC 61850-9-2 Standard - Palizban, Omid; Mekkanen, Mike; Kauhaniemi, Kimmo (The Institution of Engineering and Technology, 2020)
In the modern power grid, communication plays a vital role in making the system more reliable and secure. The communications network transfers data between different units to a control center or to Intelligent Electric Devices (IEDs) in order to accurately control or protect the modern power system. The paper discussed possible ways to monitor the measured values for protecting the power system according to IEC 61850-9-2 (sample value). The sequence of the process consists of streaming the sample value packet, decoding it, and phasor extraction and filtering, which are discussed here. To validate the research, Sundom Smart Grid was used as a pilot to measure the values converted to digital form (IEC 61850-9-2) and to stream it to the system through a highly secure communications network. To decode the SV packet, two scenarios are presented in the case study, based on processing useful features of the IEC 61850-9-2 standard-based raw data streamed from the SSG, including μPMU in a range of embedded instruments and a real-time simulator. The main result of this paper is an algorithm for analyzing SV packets and determining whether the network is operating normally.
Keywords: Distribution Network; Power system measurement and metering; Power system protection; fi=Sähkötekniikka|en=Electrical Engineering|